2006
DOI: 10.1108/09653560610654338
|View full text |Cite
|
Sign up to set email alerts
|

The drinking water response to the Indian Ocean tsunami, including the role of household water treatment

Abstract: Purpose -To document the drinking water component of the humanitarian response to the Great Sumatra-Andaman earthquake of December 26, 2004, including a focus on the promotion of household water treatment (HHWT)/safe storage to minimize the spread of diarrhoeal disease. Design/methodology/approach -Firsthand accounts of the response effort, interviews, and literature review. Findings -The combined efforts to mobilize a drinking water response were timely, comprehensive and effective. HHWT/safe storage efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…2 These coverage results are consistent with qualitative data obtained after the 2004 Indian Ocean tsunami. 24 Investigators found that, with the possible exception of boiling, HWTS did not play a significant role in the acute phase of the emergency response. As in Haiti, tanker truck water played a leading role, because most responders found that providing HWTS was not a suitable intervention.…”
Section: Discussionmentioning
confidence: 99%
“…2 These coverage results are consistent with qualitative data obtained after the 2004 Indian Ocean tsunami. 24 Investigators found that, with the possible exception of boiling, HWTS did not play a significant role in the acute phase of the emergency response. As in Haiti, tanker truck water played a leading role, because most responders found that providing HWTS was not a suitable intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Pū R w has been distributed in tsunami-affected areas (Clasen et al 2006), and in response to the recent earthquake in Kashmir.…”
Section: Discussionmentioning
confidence: 99%
“…Filtration, chlorination, combined flocculation, solar disinfection and boiling are amongst different methods found to be effective to improve the quality of drinking water in disaster situations [23]. Membrane based water purification systems have been found to have good prospects in terms of size and water quality (both input and outputs) [24] and were chosen for the EEM.…”
Section: The Water Purification Unitmentioning
confidence: 99%